THE ANALYSIS OF IMPORTANCE MANAGEMENT STUDENTS TO IMPROVE THE QUALITY OF EDUCATION - Candra Manik (FIP Unimed, 2016)
ABSTRACT This article aims to determine the quality of education in the management of learners. In the era of globalization characterized by fierce competition coupled with the growth and development demands of the democratization of education, accountability, quality and quality assurance demands of the working world, especially the world of education. These conditions require schools and educators and teachers to have reliable quality and as a result the quality assurance process conducted education. Along with the various demands of the quality of government has given rise to various laws and regulations that basically guarantees the quality of educators in managing learners. To improve the competitiveness of graduates as well as other academic products, this among others is achieved through improving the quality of education. Improving the quality of education one can do with good management of learners. With this quality of an education that can be achieved. Key words: Education, Management, Quality